Determinants and impacts of financial literacy in Cambodia and Viet Nam - Peter J. Morgan; Long Q. Trinh (Journal of Risk and Financial Management, 2019)
Our paper extends the literature on the determinants and impacts of financial literacy by conducting the OECD/INFE survey in two relatively low-income Asian economies-Cambodia and Viet Nam-and analyzing the determinants of financial literacy and the effects of financial literacy on savings and financial inclusion. Generally, our study corroborates the findings of studies of other countries, but uncovers some differences as well. The main determinants of financial literacy are found to be educational level, income, age, and occupational status. Both financial literacy and general education levels are found to be positively and significantly related to savings behavior and financial inclusion, and these results generally hold even when correcting for possible endogeneity of financial literacy.
Keywords: 330; financial literacy; financial inclusion; household saving; Cambodia; Viet Nam